2007
DOI: 10.1002/jcu.20409
|View full text |Cite
|
Sign up to set email alerts
|

Fryns syndrome: Case report and review of the literature

Abstract: Fryns syndrome (FS) is a rare malformation. We report a case of FS referred to our clinic at 27 weeks' gestation with a diagnosis of congenital diaphragmatic hernia. Sonographic examination of the fetus revealed a left-sided diaphragmatic hernia, pulmonary hypoplasia, and a median orofacial cleft. The diagnosis of FS was made after exclusion of chromosome aberrations and delivery of the fetus. Macroscopic inspection revealed a coarse face (hypertelorism and broad and flat nasal bridge, anteverted nostrils, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…KAZN, a component of the cornified envelope of keratinocytes [35], and the elastase 2A gene, CELA2A, which is involved in skin barrier function and localized in keratohyalin [36]. Returning to the co-mention analysis, interestingly we see that there is one PubMed article that co-mentions all of these phenotypes, for a disorder named Fryns syndrome [37].…”
Section: Plos Geneticsmentioning
confidence: 96%
“…KAZN, a component of the cornified envelope of keratinocytes [35], and the elastase 2A gene, CELA2A, which is involved in skin barrier function and localized in keratohyalin [36]. Returning to the co-mention analysis, interestingly we see that there is one PubMed article that co-mentions all of these phenotypes, for a disorder named Fryns syndrome [37].…”
Section: Plos Geneticsmentioning
confidence: 96%
“…In particular, distal limb malformations, which seem to be a strong key to the diagnosis when associated with CDH, were not detected in prenatal diagnosis even in a tertiary center. By reviewing the 11 cases of the prenatal diagnosis of FS in the scientific literature, we found that most of them (eight) fell into the atypical group spectrum according to the diagnostic criteria proposed by Lin et al . having only two out of six required criteria based on the prenatal observation.…”
Section: Clinical Features Of the Five Cases In The Present Study Andmentioning
confidence: 99%
“…A very few cases (11) of prenatal diagnosis for FS have been reported since 1988. 1,[11][12][13][14][15][16][17] As far as we can tell, the prenatal phenotype of this condition has never been described in detail, and recent literature is lacking.…”
mentioning
confidence: 99%